The Role of Service Quality and it Readiness in Tax System Adoption - Dewi, Sari; Anderson; Halim, Joice; Yopie, Santi; Santoso, Erizal Wibisono (Global Financial Accounting Journal, 2025)
Purpose – This study investigates the influence of tax service quality, taxpayer information technology readiness, and perceived ease of use on the implementation of the online tax system in Indonesia. The research seeks to address how these factors drive individual taxpayers’ adoption of the online system, which is crucial for enhancing tax compliance and government revenue collection. Research Method – The study employs a quantitative research design using primary data collected through surveys. Data were analyzed with SmartPLS 3.0 to test the relationships between tax service quality, information technology readiness, perceived ease of use, and online tax system implementation. Findings – The results show that tax service quality and taxpayer technology readiness have a positive and significant effect on the use of the online tax system. However, perceived ease of use does not significantly affect its adoption. This indicates that while taxpayers value service quality and their own technological readiness, usability alone does not strongly determine system usage. Implication – The findings highlight the need for policy initiatives to improve taxpayers’ digital literacy, provide intensive training and public education, and enhance the design of user-friendly tax platforms. By strengthening service quality and supporting technological readiness, tax authorities can increase taxpayer participation in the online system, ultimately boosting tax compliance and national revenue in Indonesia.